2020
DOI: 10.1155/2020/2968174
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Complications of Dental Trauma and Associated Factors: A Retrospective Study

Abstract: Objective. The aim of this work was to study the incidence of complications of dental traumatisms and look for associations between factors related to trauma and the occurrence of complications. Materials and Methods. It is a longitudinal retrospective study on a sample of 125 traumatized teeth. The sample is taken from patients consulting the dentistry service at the hospital Sahloul Sousse between 2014 and 2017. Criteria for including a patient were presence of a permanent incisor affected by a subluxation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 16 publications
(19 reference statements)
3
44
0
7
Order By: Relevance
“…Falls constituted the main etiological factor (53.6%), followed by sports (20.9%) and collisions (13.4%). Similar findings are reported in the literature [6,38].…”
Section: Discussionsupporting
confidence: 93%
“…Falls constituted the main etiological factor (53.6%), followed by sports (20.9%) and collisions (13.4%). Similar findings are reported in the literature [6,38].…”
Section: Discussionsupporting
confidence: 93%
“…Fall was the most common reason for dental trauma in the present study. Several previous studies locally and globally reported similar findings [ 16 , 18 , 19 , 22 , 30 , 31 ]. In addition, accidental hit by an object was the second most common reason for dental trauma in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…Our study also showed that only 10.8% of the participants visited a dental clinic, and 4.7% received dental treatment immediately. In addition to various aspects of poor quality of life, dental trauma can lead to clinical complications such as external root resorption, ankylosis, and pulp necrosis [ 30 ]. Nevertheless, a low prevalence of treatment for dental trauma in our study could be related to low priority for oral health, lack of awareness about the availability of dental care, and expensive dental trauma treatment in addition to sociodemographic variables.…”
Section: Discussionmentioning
confidence: 99%
“…Con relación a la causa más frecuente fue el choque con objetos seguido por caídas. En la literatura hay estudios similares a estos resultados como es el caso de Kallel et al 23 que obtuvo un 40% en caídas, siendo la más frecuente, seguida de accidentes de tránsito y laborales. El estudio de Pelli et al 8 muestras que las caídas fueron 49.7% y 18.4% colisión con objetos.…”
Section: Resultsunclassified